ROLE AND DETERMINANTS OF SMALLHOLDER FARMERS SAVING: THE CASE OF ABOBO DISTRICT, GAMBELLA REGION, ETHIOPIA - Tsehaye, Zenawit (Journal of Agri Socio Economics and Business, 2024)
Saving can be an important support scheme for smallholder farmers this is because as a tool of financial security, risk management and growth saving is essential instrument which has the potential to affect individual’s wellbeing. A two-stage simple random sampling method was used to select 206 sample respondents. Then primary data were collected through interview schedule and FGD. The study employed descriptive statistics and double hurdle model for data analysis. Based on descriptive analysis results, saving plays a meaning full role for farm households by being a financial means to deal with unexpected issues, acquiring assets, providing basic needs, to have access to different agricultural inputs, to expand their agricultural activities and for their children education. In line with this; as a result of first stage of double-hurdle model educational status, farm-income, total land owned, age of the household head and household expenditure are significant factors which affect farmers saving decision while according to the result of the second hurdle farmers level of saving significantly affected by gender, education status, farm income, off-farm income, marital status, family size and distance to financial institution of sample households. Then the study suggests the concerned body should be focused on improving farmers’ education, production, infrastructure and financial service provision.